ANALYZING FOREX MARKET PRICES USING THE CIRCULAR SHAPE AND THE HEXAGONAL STAR FOR DIGITAL AND CHRONOLOGICAL ANALYSIS EXCHANGE RATE ANALYSIS (GBP/USD) - Prof. Dr. Hashim Jabbar Al-Husseini; Prof. Dr. Haider Abbas Al-Janabi; Muhannad Rashid Sharqi Al-Majidi (Scholars Digest Publishing, 2025)
This research aims to study the behavior of the prices of the GBP/USD currency pair in the foreign exchange market, by applying unconventional tools for time technical analysis, by using specifically the pie shape and the six-point star, as tools that help to understand the role of time in determining price turning points. The theoretical framework of the study was built on the premise that the prices of the Forex market do not move randomly, but follow patterns and shapes that are affected by time and geometric factors. Therefore, the circular shape was used to draw complete time cycles, and the six-point star as a geometric model to determine time angles in order to identify possible reversal points in the market movement and entry and exit times and take profits in the market based on the GannZilla platform and the MetaTrader 4 platform. The results showed that time price angles can be an effective tool for identifying price movements in the market, such as reversal points, support and resistance levels, as well as their accuracy in predicting future trends when combined with other technical analysis tools such as the Relative Strength Index (RSI) or (MACD). The research ended with recommendations, the most important of which is to rely more on time price angles in stable markets or when trading on longer time frames. It is also recommended to use the hybrid analysis method, as price angles are combined with astronomical analysis. This will enable more accurate predictions based on multiple analytical methods. In the future, researchers also recommend expanding the study to other markets (such as stocks or commodities) to test the effectiveness of time price angles in different financial markets.
Keywords: Time analysis, forex market, time cycles, Gann theory.